Tuning intrinsic lithiophilicity of copper foil to improve electrochemical performance of anode-free Li metal battery - Natarajan, Karthic; Wu, She–Huang; Wu, Yi–Shiuan; Chang, Jeng-Kuei; Jose, Rajan; Yang, Chunchen (Elsevier Ltd, 2024)
Anode-free lithium metal batteries (AFLMBs) are currently attracting significant research attention due to their innovative lithium metal-free design. With a targeted N/P ratio of 0, AFLMBs rely exclusively on the cathode as the source of Li+ ions. Despite their potential to outperform traditional Li-ion batteries and emulate the performance of Li metal batteries, AFLMBs face a critical challenge stemming from the insufficient wettability of current collectors (CCs), such as copper (Cu) foil, by Li metal. This poor wettability results from a mismatch between the planes of CCs and Li, leading to uneven solid electrolyte interphase (SEI) growth and dead Li or dendritic lithium formation. To address this issue, we improve the Cu foil surface's affinity for lithium by subjecting it to a simple annealing process at 600 ◦C in a 5 % H2/Ar gas environment. This process effectively increases the Cu(200) planes, resulting in what we term single-faceted copper (SF-Cu). The lithiophilic SF-Cu demonstrates robust cycling performance, retaining 50.14 % of its initial capacity after 65 cycles with an impressive 98.95 % Li inventory retention rate (LIRR) in an AFLMB utilizing LiNi0.8Co0.1Mn0.1O2 (NCM811) as the cathode. Our as-prepared SF-Cu electrode emerges as a promising candidate for high-energy, anode-free Li metal battery applications.